Improving the Quality of Product Packaging Using the Six Sigma Method - Sufa, Mila Faila; Ambarsari, Rima (Universitas Muhammadiyah Surakarta, 2020)
This study aims to identify the types of defects that occur in the powder packaging process at PT. Marimas Putera Kencana as an effort to improve product quality. By doing this research, the benefits obtained include being able to know what problems are causing disabilities and can overcome these disabilities from the suggestions given by researchers. Multi-line machine is a packaging machine that is the object of research because in the packaging process using this machine there are still many defective products produced. The method used in this study is Six Sigma with the DMAIC approach which consists of Define, Measure, Analyze, Improve, Control stages. The results of data processing showed that the sigma level value was 4.10, which means that the quality control process carried out by the company was running well. However, more intense control is still needed to minimize the magnitude of the possibility of defects. Factors that cause leaking defects in primary packaging Marimas powder include four factors, namely Human, Machine, Method and Material factors. Then from the four factors given suggestions for improvement actions.